Differences in physical and technical-tactical performance between playing positions in female soccer players in FIFA competitions - Villaseca‐Vicuña, Rodrigo; Segueida-Lorca, Álvaro; Salazar-Orellana, Cristian; Valenzuela-Contreras, Luis; Cortés-Roco, Guillermo; Pérez-Contreras, Jorge; Merino-Muñoz, Pablo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to compare physical and technical-tactical performance between playing positions in official FIFA matches in elite female soccer players. A total of 39 official FIFA matches were analyzed (31 international friendlies, 3 from the 2019 World Cup in France, 2 Olympic playoffs and 3 2021 Olympic games) in 23 field players divided into 5 central defenders (DFC), 9 lateral defenders (DFL), 5 midfielders (MC) and 4 forwards (DL) from an elite national soccer team. Age = 27 ± 3.4 years; height = 162.4 ± 4.3 cm, body mass = 59.5 ± 4.6 kg. The study variables considered physical aspects such as total distance (DT), distance at high intensity (DAI), number of spikes (NP), maximum speed (VM), Playerload (PL), number of accelerations (AC) and decelerations (DES) and from the technical-tactical aspects, the offensive phase was analyzed (that is, in possession of the ball), number of passes (NPA), number of effective passes (NPAE) and percentage of effective passes (%PPAE). On the contrary, in the defensive phase (that is, without possession of the ball) number of duels (NDU), number of effective duels (NDUE) and percentage of effective duels (%DUE). The results of the study regarding the physical variables DT, PL, AC and DES showed significant differences (p < .05) with a large effect size and in the technical-tactical performance NPA, NPAE, NDU and PDUE showed significant differences (p < .05) with a large effect size between playing positions. The main conclusion is that the central defense position presented a lower amount of total distance, but a greater number of duels won and effective passes compared to the rest of the positions. Therefore, there are physical and technical-tactical differences between playing positions.